Microbiological and Periodontal Status of Patients Enduring Orthodontic Treatment - Saima Sameer Quraeshi, Mudassir Hussain, Shazia Sarwat Iqbal, Shajia Haider, Saba Parveen Soomro, Imran Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To ascertain the probing depths, plaque scores and organism morphotypes in patients enduring orthodontic treatment, as well as the benzoyl-DL-arginine-naphthylamide test scores of periodontopathic bacteria, counting those of red complex bacteria Treponema denticola, Tannerella forsythia and Porphyromonas gingivalis. Place and Duration: In the Department of Community and Preventive Dentistry, Karachi Medical and Dental College, Karachi for one-year duration from January 2022 to December 2022. Methods: Plaque samples were taken from 26 patients in this prospective research at baseline and followed up at 30 days and four months following treatment after the appliance was removed. The periodontal pathogens were found using a benzoyl-DL-arginine-naphthylamide assay. The morphotypes were identified using dark field microscopy. At each test interval, the probing depths and O'Leary Plaque Index were evaluated to identify the patients' oral health and periodontal status. The Tukey's Honestly Significant Difference test and analysis of variance were used to analyze the data. Results: After the insertion of orthodontic appliances, there were significant rise in the probing depths, plaque score, and scores of benzoyl-DL-arginine-naphthylamide at each follow-up visit. But, after the appliances were removed, the levels went back to normal. Increases in large spirochetes (2.5%), small spirochetes (8.1%), fusiforms (6%), filaments (1%) and non-motile rods (10%) were observed during orthodontic therapy, according to dark field microscopy. Conclusion: Plaque accumulation, probing depth, and microbial activity are all higher in patients receiving orthodontic treatment, which may be a sign of periodontal destruction. The probing depth, benzoyl-DL-arginine-naphthylamide test score and plaque score all came back to baseline levels thirty days after the orthodontic appliance was removed. Keywords: Porphyromonas gingivalis, orthodontic brackets, bacterial adherence, and Treponema denticola.